Eddy‐Modified Iron, Light, and Phytoplankton Cell Division Rates in the Simulated Southern Ocean. Issue 6 (2nd June 2020) - Rohr, Tyler; Harrison, Cheryl; Long, Matthew C.; Gaube, Peter; Doney, Scott C.
Abstract : We examine the effects of Southern Ocean eddies on phytoplankton cell division rates in a global, multiyear, eddy‐resolving, 3‐D ocean simulation of the Community Earth System Model. We first identify and track eddies in the simulation and validate their distribution and demographics against observed eddy trajectory characteristics. Next, we examine how simulated cyclones and anticyclones differentially modify iron, light, and ultimately population‐specific cell division rates. We use an eddy‐centric, depth‐averaged framework to explicitly examine the dynamics of the phytoplankton population across the entire water column within an eddy. We find that population‐averaged iron availability is elevated in anticyclones throughout the year. The dominant mechanism responsible for vertically transporting iron from depth in anticyclones is eddy‐induced Ekman upwelling. During winter, in regions with deep climatological mixed layer depths, anticyclones also induce anomalously deep mixed layer depths, which further supply new iron from depth via an increased upward mixing flux. However, this additional contribution comes at the price of deteriorating light availability as biomass is distributed deeper in the water column. Therefore, even though population‐averaged specific division rates are elevated in Southern Ocean anticyclones throughout most of the year, in the winter, severe light stress can dominate relieved iron stress and lead to depressed division rates in some anticyclones, particularly in the deep mixing South Pacific Antarctic Circumpolar Current. The opposite is true in cyclones, which exhibit a consistently symmetric physical and biogeochemical response relative to anticyclones. Key Points: In the Southern Ocean, cyclonic and anticyclonic eddies preferentially exhibit depressed and enhanced iron concentrations, respectively Eddy‐induced Ekman pumping is the dominant vertical transport mechanism for anomalous iron in these eddies Cyclones and anticyclones exhibit depressed and enhanced phytoplankton cell division rates, respectively, except in deep mixing waters